In vitro studies of dermally absorbed Cu(II) tripeptide complexes as potential anti-inflammatory drugs - Vicatos, Giselle M (Department of Chemistry, 2016)
Copper(II) complexes have anti-inflammatory properties which can alleviate the symptoms of rheumatoid arthritis (RA) and thus control the progression of the disease. In this study two tripeptides, namely sarcosyl-L-leucyl-phenylalanine (Sar-Leu-Phe) and glycyl-L-leucyl-phenylalanine (Gly-Leu-Phe) were studied as potential chelators, which would increase the bioavailability of copper(II) through dermal absorption. Glass electrode potentiometry was used to measure the solution thermodynamics of copper(II), nickel(II) and zinc(II) with Gly-Leu-Phe and Sar-Leu-Phe, at 25 0.01 °C and an ionic strength of 0.15 M (NaCl). The terminal amine of both tripeptides was found to have the same basicity, but the methyl group on the terminal amine decreased the stability constants of the copper(II) ligand species by 0.38 to 1.67 log units. It increased the stability constants of the zinc(II) ligand species by 0.13 to 1.07 log units and it also increased the stability constant of the NiL2H-1 species by 1.3 to 1.4 log units, while not affecting the NiL species. The solution structures of the complexes were determined spectroscopically using Ultraviolet-visible spectrophotometry, Infrared spectroscopy and 1H NMR spectroscopy. The copper(II) complexes tend more towards a square planar geometry, rather than the expected tetragonally distorted octahedral geometry. All the nickel(II) species, were square planar, except for the ML species, which was octahedral. The ligand coordinated to the metal ion via an amine-N, two amide-Ns, two carbonyl-Os and a carboxyl-O. The postulated coordination modes were validated using quantum mechanical calculations. Two methods were used to study percutaneous skin absorption, namely octanol/water partition coefficients and Franz cell permeation.